2011
DOI: 10.1128/jb.00970-10
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the RluD Pseudouridine Synthase Has Minimal Effects on Growth and Ribosome Function in Wild-TypeEscherichia coliandSalmonella enterica

Abstract: The Escherichia coli rluD gene encodes a pseudouridine synthase responsible for the pseudouridine (⌿) modifications at positions 1911, 1915, and 1917 in helix 69 of 23S rRNA. It has been reported that deletion of rluD in K-12 strains of E. coli is associated with extremely slow growth, increased readthrough of stop codons, and defects in 50S ribosomal subunit assembly and 30S-50S subunit association. Suppressor mutations in the prfB and prfC genes encoding release factor 2 (RF2) and RF3 that restore the wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…E. coli MC323 (F Ϫ Ϫ lacZ521 [Tn10 linked] rph-1) was the host strain used for recombineering and screening for accuracy-altering mutations. MC361 [F Ϫ ara ⌬(gpt-lac)5 thi prfB (from E. coli B)] carries the fully active A246 RF2 allele (16) and was used for reconstruction of the selected mutants. Plasmids pKD46, pKD4, and pCP20 were used in recombineering (17).…”
Section: Methodsmentioning
confidence: 99%
“…E. coli MC323 (F Ϫ Ϫ lacZ521 [Tn10 linked] rph-1) was the host strain used for recombineering and screening for accuracy-altering mutations. MC361 [F Ϫ ara ⌬(gpt-lac)5 thi prfB (from E. coli B)] carries the fully active A246 RF2 allele (16) and was used for reconstruction of the selected mutants. Plasmids pKD46, pKD4, and pCP20 were used in recombineering (17).…”
Section: Methodsmentioning
confidence: 99%
“…Inactivation of rluD encoding pseudouridine synthase was initially shown to have a negative effect on E. coli growth and ribosome function; however, a recent study demonstrated that rluD mutants are unstable and quickly give rise to suppressors (O'Connor & Gregory, 2011). The rluD suppressor mutations were found in pfrB and prfC encoding release factor 2 (RF2) and release factor 3 (RF3), respectively (O'Connor & Gregory, 2011).…”
Section: The Current E Coli Essential Gene Setmentioning
confidence: 99%
“…The rluD suppressor mutations were found in pfrB and prfC encoding release factor 2 (RF2) and release factor 3 (RF3), respectively (O'Connor & Gregory, 2011). The investigation of unknown essential genes, particularly assigning function to the short ORFs encoding essential proteins of 50 or fewer amino acids, is challenging.…”
Section: The Current E Coli Essential Gene Setmentioning
confidence: 99%
“…Mutations in the genes prmB (encoding class-I release factor RF2) and rpsG (encoding ribosomal protein S7) represent two well-characterized examples. O' Connor et al have reported that in all K-12 strains of E. coli, RF2 carries a threonine residue at position 246 as opposed to alanine, which is typically found at this position in the majority of bacterial RF2 proteins (O'Connor & Gregory, 2011). In the case of rpsG, a point mutation alters its canonical UGA stop codon to a leucine codon (Schaub & Hayes, 2011).…”
Section: Advantages Of Using S Typhimurium As a Modelmentioning
confidence: 99%